Reprint: Good laboratory practice: preventing introduction of bias at the bench. - Macleod, MR; Fisher, M; O'Collins, V; Sena, E; Dirnagl, U; Bath, P; Buchan, A; Buchan, A; van der Worp, H; Traystman, R; Minematsu, K; Donnan, G; et al. (Nature Publishing Group, 2009)
As a research community, we have failed to show that drugs, which show substantial efficacy in animal models of cerebral ischemia, can also improve outcome in human stroke. Accumulating evidence suggests this may be due, at least in part, to problems in the design, conduct, and reporting of animal experiments which create a systematic bias resulting in the overstatement of neuroprotective efficacy. Here, we set out a series of measures to reduce bias in the design, conduct and reporting of animal experiments modeling human stroke.